Feasibility Analysis Of Financing Subsidized Mortgage Customers at Bank BTN Syariah Makassar Branch - Ismawati; Trimulato; Herman , Nurmelianda (International Journal of Islamic Business and Management Review, 2022)
Purpose – The purpose of this research is to analyze of financing subsidized mortgage customers at Bank BTN Syariah Makassar Branch.Methodology/approach – This study uses a qualitative method. They are using a data analysis approach using the 5C+1S principle. Findings – The study results found that Bank BTN Syariah Makassar Branch principle 5C + 1S in conducting customer financing feasibility analysis. Character, Capacity and Collateral are these three points that influence the ongoing financing. Meanwhile, capital and conditions of the economy are only supporting aspects because both of them do not have a significant influence in the process of providing funding, while in Sharia, namely 1 S, more emphasis is placed on the sale and purchase contract, where this Islamic bank prioritizes MUI fatwa decisions and must meet Sharia elements.Novelty/value – the research contribution is to provide analysis of financing subsidized mortgage customers at Bank BTN Syariah with using the 5C+1S principle.